The acquisition of Spanish pronunciation by Welsh learners: transfer from a regional variety of English into SpanishThe acquisition of Spanish pronunciation by Welsh learners: transfer from a regional variety of English into Spanish - Herrero de Haro, Alfredo (Círculo de Lingüística Aplicada a la Comunicación, 2016)
Language teachers agree that the phonetic/phonological distance between a learner’s L1 and L2 is of vital importance in mastering the sounds of the L2; however, no attention is given to the phonetic/phonological distance between the regional variety of the speaker’s L1 and the L2. After comparing linguistic peculiarities of English, and of Welsh English in particular, with Castilian Spanish, the author proceeds to study the interlanguage of advanced students of Spanish from Wales. This helps to explain positive and negative transfer from this variety of English into Spanish and assists in producing a catalogue of the interferences to be corrected. Finally, using coarticulatory processes, the author presents a list of exercises to eliminate some of the interferences found in Welsh learners of Spanish. A descriptive analysis of the learners’ interlanguage shows that the phonetic/phonological distance between the regional variety of the speaker’s L1 and the L2 is what will influence this learning process the most.